Junior High School Students’ Mathematical Communication in the Written Answers Problem - Buhaerah, Buhaerah; Nasir, Muhammad (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
The mathematical communication of junior high school students is contained in written answers to mathematics, especially in finding patterns of problem-solving, presentation, and rewriting using the language, which is the purpose of this research. Expressing a mathematical situation into a mathematical model in writing can be done by reading and understanding the problem repeatedly, making connections between mathematical concepts and relevant images, making observations on the pictures given, then sorting the numbers based on the views, providing a complete explanation. Then ask students to illustrate the correct and correct answers in their language. The need to pay attention and maximize the time for students to communicate their findings. Creating a learning atmosphere that supports mathematical communication by getting students to dare to express opinions or ideas related to lessons and enrich themselves by seeking information from various sources.Komunikasi matematis siswa SMP yang terkandung dalam jawaban tertulis matematika, terutama dalam menemukan pola pemecahan masalah, penyajian, dan penulisan ulang menggunakan bahasanya. Menyatakan situasi matematika ke dalam model matematika secara tertulis, dapat dilakukan dengan cara membaca dan memahami masalah secara berulang-ulang, membuat hubungan antara konsep matematika dan gambar yang relevan, melakukan pengamatan pada gambar yang diberikan, kemudian mengurutkan angka berdasarkan gambar, memberikan penjelasan yang lengkap, kemudian meminta siswa untuk mengilustrasikan jawaban dalam bahasa mereka sendiri yang benar dan benar. Perlunya memperhatikan dan memaksimalkan waktu bagi siswa untuk mengomunikasikan temuannya. Menciptakan suasana belajar yang mendukung komunikasi matematis dengan cara membiasakan siswa memberanikan diri mengemukakan pendapat atau gagasan terkait pelajaran, dan memperkaya diri dengan mencari informasi dari berbagai sumber.